2005
DOI: 10.1167/iovs.04-1426
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Corneal Sensitivity in Patients with Dry Eye

Abstract: Patients with dry eye exhibit corneal hypoesthesia after mechanical, thermal, and chemical stimulation that appears to be related to damage to the corneal sensory innervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 20 publications
9
162
0
4
Order By: Relevance
“…This can be explained by another factor that may complicate the assessment of OSD using OSDI and it is corneal hypoesthesia. Corneal sensitivity tends to decrease with age but it is also a consequence of long-term effect of preservativecontaining antiglaucoma eye drops on corneal surface [19,20]. The chronic patients have less innervation of the ocular surface and as a consequence experience less pain and discomfort which can result in slightly better OSDI score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by another factor that may complicate the assessment of OSD using OSDI and it is corneal hypoesthesia. Corneal sensitivity tends to decrease with age but it is also a consequence of long-term effect of preservativecontaining antiglaucoma eye drops on corneal surface [19,20]. The chronic patients have less innervation of the ocular surface and as a consequence experience less pain and discomfort which can result in slightly better OSDI score.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were grouped into 4 categories by OSDI score: normal (scores 0-12), mild OSD symptoms (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate OSD symptoms (23-32), severe OSD symptoms (33-100) [13]. Patients' medical records were used to obtain medical history including detailed data on the use of medication and duration of therapy.…”
Section: Clinical and Experimental Ophthalmologymentioning
confidence: 99%
“…[12][13][14][15][16] Other studies however did not find any sex difference in corneal sensitivity. 17,18 Future studies are needed to confirm and further explore these differences, but also to clarify the exact role of ocular surface sensitivity in the symptomatology of DED.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In those groups with such an instrument, most have found decreased sensitivity to all three stimuli in dry eye patients. 105,106 However, some groups have found higher sensitivity to air flow in dry eye patients, 107,108 representing a different disease subtype or patients at different points on the disease continuum. Commercially available confocal microscopy units have identified that some dry eye patients have neuronal alterations in the corneal subbasal plexus structures.…”
Section: Neuropathic Ocular Pain and Implications For Dry Eye Diagnosismentioning
confidence: 99%